(untitled) (Journal of Information Technologies in Education (ITE), 2015)
Wide involvement of children of primary school age to information and communication environment requires the creation of a scientific substantiated system of childs integration in to this environment. The article deals with the issue of using media education for primary school pupils preparing for life in the modern information age, the perception of different information, obtaining the ways of communication on the basis of non-verbal communication forms by technical means. Involving primary school pupils to computer technologies highlights the issue of their socialization in the information environment. The article deals with the process of socialization as a process of an individual integration into society by mastering his or her elements of culture, social norms and values, which are formed on the basis of socially significant features of a person.Generalization of researches, existing experience let identify the main directions of a teacher’s activity for successful socialization of a primary school pupil in modern information andcommunication environment.